PERAN WANITA TANI DALAM SOSIAL EKONOMI KELUARGA DI SUKO REJO KELURAHAN LEMPAKE KOTA SAMARINDA (The Role of Farmer Woman in the Socio Economic Family in Suko Rejo Lempake Urban Village Samarinda City) - ARIF HIDAYAT; MIDIANSYAH EFFENDI; ACHMAD ZAINI (Universitas Mulawarman (University of Mulawarman), 2020)
This study aimed to know the role of farmer woman in socio economic family. The location of research was in the Suko Rejo, Lempake Urban Village, Samarinda City with a total of 25 respondents. Data were analyzed by method of descriptive. The results of this research showed that farmer woman in Suko Rejo, Lempake Urban Village, Samarinda City works as tailor, vegetable seller, opening food stalls at home, washing worker, farm labor, farmer, and as caregiver. Farmer woman gives contribution as family income and it increases family welfare. Factors cause farmer woman working such as the high of daily need, the small of husband income, the responsibility in household, and the use of free time.